Implementação da codificação analógica paramétrica para aplicação em redes de sensores sem fio - Schroeder, Rafaela (2017)
This work presents the parametric analog coding as an alternative to overcome common problems in digital transmission. To achieve this, the method performs the codification together with the adapter and canal in only one stage, so that the delay in communication is minimized – contrary to what happens in a digital system, which uses long blocks of redundancy in the codification of a canal to approximate the theoretical limit performance. Therefore, a sample with two coordinates is compressed in just one, which is an angle of the spiral of Archimedes. The implementation has occurred using an audio signal that was transmitted by sound card. This channel of communication presents several adversities to the transmission, such as the analog-to-digital conversions and the processing limit. To evaluate the performance of the proposed method, two distinct values of sampling frequency were applied: the original frequency of the signal and the frequency divided by two, due to compression. In this way, a comparison was made between the two scenarios through the calculation of the rate of the signal distortion and through the frequency spectrums, where is possible to notice the noise on the received signal.